Outcome-impact survey on the public awareness & appreciation programme and traditional knowledge documentation programme of Sarawak biodiversity centre / Voon Boo Ho... [et al.] - Voon, Boo Ho; Hamali, Jamali; Chan, Margaret Kit Yok; Jaya, Serah (2014)
Outcome and impact evaluations for important service organisations such as Sarawak Biodiversity Centre is crucial in ensuring high quality policymaking and effective service operations management. A continuous and consistent emphasis on serving the targeted customer groups as well as the general public will always be necessary for excellent and sustainable biodiversity conservation and development in Sarawak. It is great to note that Sarawak Biodiversity Centre's core functions are generally wellregarded and respected towards Sarawak's biodiversity excellence. This six-month state-wide questionnaire survey which focuses on evaluating the Awareness & Appreciation Programme and Traditional Knowledge Documentation Programme of the Centre has found numerous favourable outcomes and impacts of the two programmes. Besides, there are also useful insights for further improvement. Sarawak Biodiversity Centre has been very actively involved in promoting Sarawak's biodiversity and educating the general public on the importance of Sarawak's biodiversity and the Traditional Knowledge related to Sarawak's biodiversity. The strategic programmes are developed and implemented accordingly. Specifically, the Awareness and Appreciation Programme helps to: i) provide opportunities for the general public to participate in the Centre's Awareness and Appreciation programme and enhance appreciation for the State's rich biodiversity and her biotechnology initiatives, ii) organize seminars and forums that focus on biodiversity-biotechnology topics, targeted at policy makers, key government officials, members of the academia, researchers and scientists, industry representatives and the media, and iii) collate and disseminate accurate and factual information on biodiversity-biotechnology to the